THE ANALYSIS OF BABY BOOMERS ACCEPTANCE AND ADAPTION OF CASHLESS SOCIETY IN MANADO - Supit, Vera G.; Pandowo, Merinda H. C.; Tumbuan, Willem J. F. A (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
Baby boomers (also known as boomers) are the demographic cohort following the Silent Generation and preceding Generation X. There are varying timelines defining the start and the end of this cohort; demographers and researchers typically use starting birth years ranging from the early to mid-1940s and ending birth years ranging from 1960 to 1964. As a group, baby boomers were the wealthiest, most active, and most physically fit generation up to the era in which they arrived, and were amongst the first to grow up genuinely expecting the world to improve with time. In order to achieve the objectives, the researcher got information from 10 informants of baby boomers and this research using a qualitative study which is in-depth interview. This research uses purposive sampling to grab and collect the answer from the informants. Based on the data analysis and discussion, the result of the research is The acceptance of the cashless society for the baby boomers is positive and the cashless payment method is very welcomed by the baby boomers, even there are some difficulty face by the baby boomers but all of them said that cashless payment method is a good payment system to follow the trend. A baby boomer's reaction towards a cashless payment is good.. They accept and do not mind with cashless payment method.. The recommendation, better to educate the baby boomers about the usage of cashless payment methods, so the baby boomers so that they are more familiar with cashless payment. Keywords: Baby Boomers, Cashless Payment